1970
DOI: 10.2135/cropsci1970.0011183x001000060043x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Subterranean Clover (Trifolium Subterraneum L.) at Very Early Stages1

Abstract: Ten unique morphological stages of plant development from emergence to full expansion of the unifoliolate leaf were described for an annual clover (Trifolium subterraneum L.). This system of classification provides for precise morphological description of plant development when a high degree of experimental resolution is required at very early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…- vantage of earlier autumn growth if rain was sufftdent for establishment. Raguse et al ( 1970) have shown that clover seedling growth rate is directly related to temperature. The earlier in the autumn a cool season clover can germinate, the more time it has to become well established and produce forage before growth is limited by low winter temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…- vantage of earlier autumn growth if rain was sufftdent for establishment. Raguse et al ( 1970) have shown that clover seedling growth rate is directly related to temperature. The earlier in the autumn a cool season clover can germinate, the more time it has to become well established and produce forage before growth is limited by low winter temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Barker') seed was inoculated with Pelinoc (Nitragin Co.) Rhizobium inoculant and sown 6-mm-deep in washed, sterile sand. The plants were thinned to 20 per pot at the 0.8 unifoliate stage of development (24). Rectangular stainless steel pots (38.1 em X 5.1 em X 20.3 em) contained a 0.5 em thick plexiglass plate pierced with 24 1.3-cm-diam holes which was supported 1.0 em• above the bottom of the pot and covered with six layers of cheesecloth to facilitate drainage and gas exchange.…”
Section: Methodsmentioning
confidence: 99%
“…A later planting in January 1971 gave lower winter mortality and increased emergence of some cultivars (Table 2). In studies of the development of subclover seedlings, Raguse et al (1970) found that full emergence of the cotyledons required about 56 days at 10?C. During mid-December, daytime maximum temperatures did not often exceed 10?C (Fig.…”
Section: Results the Seeded Clovers Germinated At The Time Of The Firmentioning
confidence: 99%